Strategi Kepala Sekolah dalam Menerapkan Pendidikan Karakter pada Siswa Sekolah Dasar - Putri Maharani Dwi Rarasati; Sisriawan Lapasere; Dyah Rahmawati; Rizal (Kelola: Jurnal Manajemen Pendidikan, 2025)
Character education is vital in m ethics. Nevertheless, several schools encounter difficulties in successfully carrying out character education. Principalh creating and directing character education initiatives to ensure their effective implementation within the school setting. This research seeks to examine the methods employed by principals to enforce character education, the execution of these methods in schools, and the resulting outcomes. A descriptive qualitative approach with a phenomenological lens is utilized for this stud the principal, teachers, and students at SD Negeri 3 Palu. Data were gathered through observations, interviews, and documentation and were analyzed through data reduction, presentation, and drawing conclusions. The validity of the data was ensured using source and method triangulation. The results indicate that principals employ a variety of strategies, including the integration of character values into educational activities, promoting positive behavior, and engaging with parents and the community. The execution of these strategies requires active involvement from both teachers and students in cultivating a character-focused school environment. The effects of these strategies include enhanced student understanding of the significance of moral and social values. Based on these results, it is suggested character development and strengthen collaboration with parents and the community to foster a more supportive atmosphere for the development of students' character.